Productivity of denominal and deadjectival suffixal nouns in the Joint Corpus of Lithuanian - Pakerys, Jurgis; Navickaitė-Klišauskienė, Agnė; Dadurkevičius, Virginijus (Baltistica, 2025)
We explore the derivational productivity of the following salient suffixes of Lithuanian denominal and deadjectival nouns on the basis of the Joint Corpus of Lithuanian (1.3 billion tokens): -um-as, -yb-ė, -yst-ė, -izm-as, -inink-as (-ė), -uol-is (-ė), -ist-as (-ė), -el-is (-ė), -ėl-is (-ė), -(i)uk-as (-ė). We estimate realized, expanding, and potential productivity (Baayen 1992; 1993) and compare our results to the productivity rankings found in the major grammars and the studies of neologisms. Our focus is on the most productive suffixes of the following categories: quality nouns, status nouns, personal nouns, and diminutives. The analysis demonstrates that in a number of cases the productivity ranking of the investigated suffixes differs from the one presented in the major grammars. Our findings are in part supported by the recent studies of neologisms and other analyses based on corpus data.
Keywords: Lithuanian; denominal nouns; deadjectival nouns; suffixal nouns; derivational productivity; realized productivity; expanding productivity; potential productivity; corpus linguistics